2015
DOI: 10.1080/03601234.2015.1062650
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of S-metolachlor, terbuthylazine, desethyl-terbuthylazine, mesotrione, flufenacet, isoxaflutole, and diketonitrile in field lysimeters as affected by the time elapsed between spraying and first leaching event

Abstract: The effect of elapsed time between spraying and first leaching event on the leaching behavior of five herbicides (terbuthylazine, S-metolachlor, mesotrione, flufenacet, and isoxaflutole) and two metabolites (desethyl-terbuthylazine and diketonitrile) was evaluated in a 2011-2012 study in northwest Italy. A battery of 12 lysimeters (8.4 m(2) long with a depth of 1.8 m) were used in the study, each filled with silty-loam soil and treated during pre-emergence with the selected herbicides by applying a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
5
15
0
1
Order By: Relevance
“…Furthermore, the maximum percentage of mesotrione residues was found in the same layer according to the soil studied (Figure 1). These data are consistent with Milan et al [5] and Marín-Benito et al [19] that reported mesotrione had high leachabilityin the soil.…”
Section: Leaching Mesotrione Alone and In A Mixturesupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, the maximum percentage of mesotrione residues was found in the same layer according to the soil studied (Figure 1). These data are consistent with Milan et al [5] and Marín-Benito et al [19] that reported mesotrione had high leachabilityin the soil.…”
Section: Leaching Mesotrione Alone and In A Mixturesupporting
confidence: 83%
“…The data corroborate with Milan et al [5], that found the leaching of mesotrione applied in mixture with S-metolachlor and terbuthylazine averaged from 24 to 39% of that initially applied to columns of 0-40 cm of sandy soil [4] and can be detected at up to 1.8 m depth silt loam soil, although this was not quantified because of the low-dose application (150 g ha −1 ) and rapid dissipation (DT50 = 3-7 days).…”
Section: Leaching Mesotrione Alone and In A Mixturesupporting
confidence: 82%
See 2 more Smart Citations
“…6b). In any case, the observed Smetolachor concentrations were higher than the 0.1 μg L −1 regulatory limit (Directive 98/83 EC 1998) which is consistent with the low value of its sorption coefficient (Table 3), and with several observations (e.g., Milan et al 2015). As for water percolation, the simulation of pesticide leaching in Lamothe was poor ( Fig.…”
Section: Performances Of Stics-macro and Macro In Predicting Pesticidsupporting
confidence: 82%